La crítica de Emmanuel Lévinas al cristianismo en Difícil libertad focalizada en los binomios justicia vs. piedad «espiritual» y Torá vs. encarnación - Alberto F. Roldán (Franciscanum, 2012)
In this article analyzes the critics that Emmanuel Levinas poses to Christianity in his work Dificil Libertad. This criticism has the centre especially in the binomials in opposition: Justice vs. “Spiritual” Piety and Tora vs. Incarnation. The author recognizes the positive aspects of the analysis of Levinas about the historical influence of Christianity but he questions the fact of oversizing the Tora as the most nearest act of God in detriment of the incarnation that Levinas considers impossible and unnecessary. In the final section of his work, discovers one possible point of confluence between Judaism and Christianity: the Messianic hope.